Building a method for the study of the mesolithic-neolithic transition in Portugal - Jackes, Mary (Documenta Praehistorica, 2004)
This paper focuses on the agricultural transition in Portugal and on demography across this transition, concentrating on two key skeletal samples, the Mesolithic shell midden of Cabeço da Arruda and the Neolithic burial cave of Casa da Moura. It extends our previous work on the demography of the transition and the methodology surrounding its determination. We explain our method for determination of the number of individuals in samples where whole skeletons cannot be used. We then concentrate on the estimation of fertility, placing it within limits of biological feasibility, sample inadequacies, and vagaries of age assessment. From our analysis, which includes an examination of historical issues with the sites, we argue for regional population continuity between 8000 and 6000 cal BP, and suggest that Neolithic life-ways slowly intensified, founded on important elements deriving from the late Mesolithic, with changes that included increased fertility through shortening of the birth interval.
Keywords: arheološke najdbe; mezolitik; neolitik; agriculture; kmetijstvo; demografski razvoj